Secondary battery and electric equipment
By using a specific composition of soft and hard carbon composite material and graphite coated hard carbon material on the negative electrode of the sodium ion battery, combined with a dual-coated structure, the problems of low energy density and cycling performance of the sodium ion battery are solved, and higher battery performance is achieved.
Patent Information
- Application Number
- CN202411849731.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-13
AI Technical Summary
Existing sodium ion batteries have problems with first-time Coulomb efficiency, cycle capacity retention and energy density.
The first active substance and the second active substance having a specific composition are employed, including a soft carbon material, a hard carbon material and a graphite coated hard carbon material, and the energy density and cycling performance of the battery are improved by the arrangement of the first coating and the second coating.
It significantly improves the energy density, first-time Coulomb efficiency and cycling performance of sodium ion batteries to meet the needs of use.
Smart Images

Figure BDA0005191314900000131 
Figure BDA0005191314900000141 
Figure BDA0005191314900000142
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of new energy materials, and specifically relates to a secondary battery and electrical equipment. Background Art
[0002] Among many new clean energy sources, sodium-ion batteries have attracted widespread attention due to their abundant raw materials and low production costs. As the negative electrode material of sodium-ion batteries, hard carbon will have irreversible capacity loss during the first discharge, which will consume a large amount of electrolyte and sodium ions released from the positive electrode, affecting the discharge capacity of the battery, thereby reducing the battery's first coulombic efficiency. At the same time, sodium-ion batteries also have problems with low cycle capacity retention and energy density, so sodium-ion batteries need to be improved to enhance their electrochemical performance and meet usage requirements. Summary of the invention
[0003] Therefore, the technical problem to be solved by the present application is to overcome the defects of the sodium ion batteries in the prior art, such as low first coulombic efficiency, cycle capacity retention rate and energy density, so as to provide a secondary battery and electrical equipment.
[0004] To this end, this application provides the following technical solutions:
[0005] According to one aspect of the present application, a secondary battery is provided, comprising a negative electrode plate, wherein the negative electrode plate comprises:
[0006] current collector;
[0007] A first coating layer, coated on at least one side of the current collector, wherein the first coating layer contains a first active material, wherein the first active material includes a soft carbon material and a first hard carbon material, and wherein the first active material contains a first element, wherein the first element includes at least one of nitrogen, sulfur, phosphorus, and silicon;
[0008] A second coating is applied on the surface of the first coating, the second coating contains a second active substance, the second active substance includes a second hard carbon material, graphite material is distributed on at least part of the surface of the second hard carbon material, the second active substance contains a second element, and the second element includes at least one of nitrogen, sulfur, phosphorus, and silicon.
[0009] In some optional embodiments, the first element includes silicon, and at least one of nitrogen, sulfur, and phosphorus;
[0010] And / or, the second element includes silicon, and at least one of nitrogen, sulfur, and phosphorus.
[0011] In some optional embodiments, based on the total mass of the first active material, the mass percentage of the soft carbon material is 20% to 50%, and the mass percentage of the first element is 1% to 5%;
[0012] And / or, based on the total mass of the second active material, the mass percentage of the graphite material is 10% to 40%, and the mass percentage of the second element is 0.01% to 3%.
[0013] In some optional embodiments, under a test pressure of 20 kN, the powder resistivity A of the first active material and the powder resistivity B of the second active material satisfy the following relationship:
[0014] 1.2≤A / B≤1.8.
[0015] In some optional embodiments, the powder resistivity A of the first active material is 5 to 12 mΩ·cm;
[0016] And / or, the powder resistivity B of the second active material is 3 to 8 mΩ·cm.
[0017] In some optional embodiments, the film resistance of the negative electrode plate is 1 to 3 mΩ.
[0018] In some optional embodiments, the Dv50 of the soft carbon material is 6 to 12 μm; the Dv50 of the first hard carbon material is 3 to 8 μm;
[0019] And / or, the Dv50 of the second active material is 8 to 14 μm.
[0020] In some optional embodiments, the first active substance and the second active substance are subjected to thermogravimetric analysis under an inert gas atmosphere, with a test temperature of 30 to 500° C. and a heating rate of 10° C. / min, satisfying:
[0021] The weight loss percentage of the first active substance in the temperature range of 200° C. to 400° C. is less than 5%;
[0022] The weight loss percentage of the second active material in the temperature range of 200° C. to 400° C. is less than 3%.
[0023] In some optional embodiments, the porosity of the first coating is 40% to 50%, and the porosity of the second coating is 20% to 30%;
[0024] And / or, based on the total thickness of the first coating layer and the second coating layer, the thickness of the first coating layer accounts for 55% to 70%.
[0025] According to another aspect of the present application, there is provided an electrical device comprising the above-mentioned secondary battery.
[0026] The technical solution of this application has the following advantages:
[0027] The secondary battery provided by the present application includes a negative electrode plate, and the negative electrode plate includes: a current collector; a first coating layer, which is coated on at least one side of the current collector, and the first coating layer contains a first active material, and the first active material includes a soft carbon material and a first hard carbon material, and the first active material contains a first element, and the first element includes at least one of nitrogen, sulfur, phosphorus, and silicon; a second coating layer, which is coated on the surface of the first coating layer, and the second coating layer contains a second active material, and the second active material includes a second hard carbon material, and the second hard carbon material has a graphite material distributed on at least part of the surface, and the second active material contains a second element, and the second element includes at least one of nitrogen, sulfur, phosphorus, and silicon. Compared with the prior art, the present application can improve the energy density of the battery, the first coulomb efficiency, and the cycle performance by selecting the first active material and the second active material with specific compositions, and coordinating the arrangement of the first coating layer and the second coating layer. Specifically, the use of soft carbon and hard carbon composite materials in combination with graphite-coated hard carbon materials can improve energy density; doping the active material with the first element and the second element can improve the conductivity of the negative electrode plate, improve the ion diffusion kinetics, and facilitate the deintercalation of sodium ions; while using a dual active material coating setting, the ion diffusion efficiency can be improved, the deintercalation of sodium ions can be accelerated, the first coulomb efficiency can be improved, and the battery cycle performance can be enhanced.
[0028] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. DETAILED DESCRIPTION
[0029] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.
[0030] As analyzed in the background technology, the sodium ion batteries in the prior art have defects such as low initial charge and discharge efficiency, cycle capacity retention rate and energy density. To solve these problems, the present application provides a secondary battery and electrical equipment.
[0031] According to one aspect of the present application, a secondary battery is provided, comprising a negative electrode plate, wherein the negative electrode plate comprises:
[0032] current collector;
[0033] A first coating layer, coated on at least one side of the current collector, wherein the first coating layer contains a first active material, wherein the first active material includes a soft carbon material and a first hard carbon material, and wherein the first active material contains a first element, wherein the first element includes at least one of nitrogen, sulfur, phosphorus, and silicon;
[0034] A second coating is applied on the surface of the first coating, the second coating contains a second active substance, the second active substance includes a second hard carbon material, graphite material is distributed on at least part of the surface of the second hard carbon material, the second active substance contains a second element, and the second element includes at least one of nitrogen, sulfur, phosphorus, and silicon.
[0035] Compared with the prior art, the present application can improve the energy density of the battery, improve the first coulombic efficiency and cycle performance by selecting a first active material and a second active material with a specific composition, and coordinating the setting of a first coating and a second coating. Specifically, the use of a soft carbon and hard carbon composite material with a graphite-coated hard carbon material can improve the energy density; doping the active material with the first element and the second element can improve the conductivity of the negative electrode plate, improve the ion diffusion kinetics, and facilitate the deintercalation of sodium ions; at the same time, the setting of a composite coating can improve the ion diffusion efficiency, accelerate the deintercalation of sodium ions, improve the first coulombic efficiency and enhance the battery cycle performance.
[0036] In the present application, the first active substance can be obtained by ball milling a mixture of coal-based soft carbon and bio-based hard carbon to obtain a soft and hard carbon composite material with a microporous structure. The first element can be doped in the composite material by physical or chemical methods. For example, sulfur, phosphorus, silicon, nitrogen and other elements can be mixed with the composite material by using materials containing sulfur, phosphorus, silicon or nitrogen as sulfur sources, phosphorus sources, silicon sources or nitrogen sources, such as sulfur powder, phosphorus pentoxide, silicon powder, urea and any other known substances containing the above elements, without limitation. It is subjected to physical ball milling to obtain a soft and hard carbon composite material with element doping. The doping method of the second element in the second active substance is the same as above. The second active substance can mix the hard carbon doped with the second element with a graphitizable material, and perform a heat treatment at 2500°C to 3000°C or above to obtain a graphite-coated hard carbon material; or, the hard carbon doped with the second element can be pretreated with a cationic surfactant and then mixed with a graphite material to obtain a graphite-coated hard carbon material. Cationic surfactants can make the surface of hard carbon positively charged, enhance the electrostatic adsorption with graphite, so as to achieve the coating of graphite on hard carbon; at the same time, surfactants also have good dispersibility and can effectively prevent hard carbon from agglomerating. Specifically, hard carbon can be added to hexadecyltrimethylammonium bromide (CTAB) with a concentration of 10 mg / mL to 20 mg / mL, stirred and soaked at room temperature for 6 hours to 10 hours, dried to obtain treated hard carbon, and the pretreated hard carbon is mixed with graphite and ball-milled to obtain graphite-coated hard carbon material.
[0037] In some optional embodiments, the first element includes silicon, and at least one of nitrogen, sulfur, and phosphorus;
[0038] And / or, the second element includes silicon, and at least one of nitrogen, sulfur, and phosphorus.
[0039] In the present application, by limiting the first element and the second element to include silicon, the energy density can be further improved. This is because silicon has a theoretical specific capacity of up to 4200 mAh / g, and is a very potential high-capacity negative electrode material. After being doped with silicon, it can provide more active sites for sodium ions, thereby further improving the energy density of the battery.
[0040] In some optional embodiments, based on the total mass of the first active material, the mass percentage of the soft carbon material is 20% to 50%, and the mass percentage of the first element is 1% to 5%; as an example, based on the total mass of the first active material, the mass percentage of the soft carbon material can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, or within the range of any of the above values; the mass percentage of the first element can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or within the range of any of the above values. In this way, the energy density of the first active material can be increased while reducing the adverse effects of volume expansion.
[0041] In some optional embodiments, the mass percentage of the graphite material is 10% to 40% based on the total mass of the second active material, and the mass percentage of the second element is 0.01% to 3%; as an example, the mass percentage of the graphite material can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, or within the range of any of the above values based on the total mass of the second active material; the mass percentage of the second element can be 0.01%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, or within the range of any of the above values. In this way, the energy density of the second active material can be increased while reducing the adverse effects of volume expansion.
[0042] In some optional embodiments, under a test pressure of 20 kN, the powder resistivity A of the first active material and the powder resistivity B of the second active material satisfy the following relationship:
[0043] 1.2≤A / B≤1.8.
[0044] As an example, a ratio A / B between the powder resistivity A of the first active material and the powder resistivity B of the second active material may be 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, or within a range of any of the above values.
[0045] In the present application, by limiting the proportional relationship between the powder resistivity A of the first active material and the powder resistivity B of the second active material, the embedding and extraction of sodium ions and the stability of the electrode structure can be improved; specifically, when A / B satisfies the above-mentioned limited range, the resistivity gradient formed inside the electrode is conducive to guiding the embedding and extraction of sodium ions in the electrode; in addition, the upper and lower active materials can also work together during the charging and discharging process to enhance the overall structural stability of the electrode.
[0046] In some optional embodiments, the powder resistivity A of the first active material is 5 to 12 mΩ·cm; as an example, the powder resistivity A of the first active material can be 5 mΩ·cm, 7 mΩ·cm, 9 mΩ·cm, 10 mΩ·cm, 12 mΩ·cm, or in the range of any of the above values. The powder resistivity A of the first active material in the above range can make the transmission of electrons in the first active material smoother, which is conducive to reducing the internal resistance of the battery. This will not only make the battery not require a higher voltage to overcome the resistance during charging and reduce the consumption of electric energy, but also increase the electric energy available for output during discharge, and improve the actual use capacity and power density of the battery. And / or, in some optional embodiments, the powder resistivity B of the second active material is 3 to 8 mΩ·cm. As an example, the powder resistivity B of the second active material can be 3 mΩ·cm, 4 mΩ·cm, 5 mΩ·cm, 6 mΩ·cm, 7 mΩ·cm, 8 mΩ·cm, or in the range of any of the above values. The powder resistivity B of the second active material in the above range can make the transmission of electrons in the second active material smoother, which is beneficial to reducing the internal resistance of the battery. This will not only make the battery not require a higher voltage to overcome the resistance during charging, thereby reducing the consumption of electrical energy, but also increase the electrical energy available for output during discharge, thereby improving the actual usage capacity and power density of the battery.
[0047] In the present application, the powder resistivity of the first active substance and the second active substance can be tested by methods and equipment known in the art. For example, the constant voltage method can be used for testing, using an annular electrode and measuring based on Ohm's law, i.e., R=U / I. The test process uses an oil pressure method with a pressure of 20 kN.
[0048] The present application can improve the insertion and extraction of sodium ions by limiting the resistivity of the powders of the first active material and the second active material, thereby ensuring the energy density and the overall performance of the battery.
[0049] In some optional embodiments, the diaphragm resistance of the negative electrode plate is 1 to 3 mΩ; as an example, the diaphragm resistance of the negative electrode plate is 1 mΩ, 1.5 mΩ, 2 mΩ, 2.5 mΩ, 3 mΩ, or within a range consisting of any of the above values.
[0050] In the present application, a dual-probe resistance method may be used for testing, specifically using two probes to contact the electrode membrane, one probe applies current, and the other probe measures voltage, and the resistance is calculated using Ohm's law.
[0051] In the present application, the membrane resistance of the negative electrode plate is within the above range, which can ensure that the plate has good conductivity, allowing electrons to move quickly inside the plate, reducing ohmic polarization, and at the same time will not cause local overheating due to excessive resistance, causing structural changes in the plate material.
[0052] In some optional embodiments, the Dv50 of the soft carbon material is 6 to 12 μm; the Dv50 of the first hard carbon material is 3 to 8 μm; as an example, the Dv50 of the soft carbon material may be 6 μm, 8 μm, 10 μm, 12 μm, or within the range of any of the above values; the Dv50 of the first hard carbon material may be 3 μm, 5 μm, 7 μm, 8 μm, or within the range of any of the above values;
[0053] And / or, in some optional embodiments, the Dv50 of the second active substance is 8 to 14 μm; as an example, the Dv50 of the second active substance may be 8 μm, 10 μm, 12 μm, 14 μm, or within a range consisting of any of the above values.
[0054] In the present application, the laser diffraction method can be used for testing. Specifically, the powder sample to be tested can be dispersed in anhydrous ethanol, and then the dispersed sample is placed in the sample cell of the laser diffraction particle size analyzer for testing. The data is processed by the built-in algorithm to determine Dv50.
[0055] The present application can improve the processing performance and electrochemical performance of the material by limiting the Dv50 of the first active material and the second active material; specifically, limiting the Dv50 of the active material to the above range can make the active material, the conductive agent and the binder better mixed together, which is conducive to forming a stable electrode structure and facilitating the sodium ion deintercalation.
[0056] In some optional embodiments, the first active substance and the second active substance are subjected to thermogravimetric analysis under an inert gas atmosphere, with a test temperature of 30 to 500° C. and a heating rate of 10° C. / min, satisfying:
[0057] The weight loss percentage of the first active substance in the temperature range of 200° C. to 400° C. is less than 5%;
[0058] The weight loss percentage of the second active material in the temperature range of 200° C. to 400° C. is less than 3%.
[0059] In the present application, through the above-mentioned limitation of the thermogravimetric analysis results of the first active substance and the second active substance, it is shown that the material has high thermal stability, thereby improving the thermal stability and electrochemical performance of the battery; specifically, limiting the thermogravimetric loss of the material within the above-mentioned range can reduce the battery performance degradation and safety hazards caused by decomposition or volatilization of the active substance, among which the first active substance has a slightly higher thermogravimetric loss (less than 5%), which can buffer the heat changes inside the battery to a certain extent, and the relatively low thermogravimetric loss of the second active substance (less than 3%) can provide better stability for the reaction interface of the battery.
[0060] In some optional embodiments, the porosity of the first coating is 40% to 50%, and the porosity of the second coating is 20% to 30%; as an example, the porosity of the first coating may be 40%, 42%, 44%, 45%, 46%, 48%, 50%, or within the range of any of the above values; the porosity of the second coating may be 20%, 22%, 24%, 25%, 26%, 28%, 30%, or within the range of any of the above values.
[0061] In the present application, the porosity test can be performed using the hexadecane absorption method. Specifically, n-hexadecane is used to infiltrate and fill the pores of the electrode to be tested, and the mass change of the electrode before and after immersion in n-hexadecane is measured. Combined with the density of n-hexadecane, the volume of the pores filled with n-hexadecane is calculated, and the porosity of the electrode coating is then obtained.
[0062] The present application limits the porosity of the first coating and the second coating to the above ranges respectively, so that the inner layer of the negative electrode plate has more pores than the outer layer of the electrode plate, which is beneficial to the infiltration of the electrolyte into the electrode plate, while the outer layer of the electrode plate has fewer pores, which can increase the electron transmission rate, reduce the probability of the conductive path being cut off by the pores, avoid obstruction of electron conduction, and reduce the ohmic internal resistance of the battery cell.
[0063] In some optional embodiments, the thickness of the first coating layer accounts for 55% to 70% of the total thickness of the first coating layer and the second coating layer. As an example, the thickness of the first coating layer may account for 55%, 58%, 60%, 62%, 65%, 67%, 70% of the total thickness of the first coating layer and the second coating layer, or within the range of any of the above values.
[0064] In the present application, by limiting the proportion of the first coating thickness, the ion transmission path can be optimized; specifically, by limiting the proportion of the first coating thickness to the above range, more sodium ions can be accommodated, and the sodium ions diffuse more slowly to the active sites, thereby reducing polarization caused by excessive local concentration.
[0065] In some optional embodiments, based on the total mass of the first coating layer, the first coating layer comprises 92% to 96% of the first active material, 2% to 4% of the first conductive agent, and 2% to 4% of the first binder;
[0066] And / or, based on the total mass of the second coating layer, the second active material comprises 92% to 96%, the second conductive agent comprises 2% to 4%, and the second binder comprises 2% to 4%.
[0067] In some optional embodiments, the first conductive agent includes one or more of acetylene black, carbon nanotubes, conductive carbon black, and composite conductive materials; optionally, the first conductive agent includes at least one of acetylene black and conductive carbon black;
[0068] And / or, the first binder includes one or more of styrene-butadiene rubber latex, carboxymethyl cellulose, polyvinylidene fluoride, polyacrylic acid, polyacrylonitrile, and polyacrylate; optionally, the first binder includes one or more of styrene-butadiene rubber latex, carboxymethyl cellulose, and polyacrylic acid.
[0069] In some optional embodiments, the second conductive agent includes one or more of acetylene black, carbon nanotubes, conductive carbon black, and composite conductive materials; optionally, the second conductive agent includes at least one of carbon nanotubes and composite conductive materials;
[0070] And / or, the second binder includes one or more of styrene-butadiene rubber latex, carboxymethyl cellulose, polyvinylidene fluoride, polyacrylic acid, polyacrylonitrile, and polyacrylate; optionally, the second binder includes at least one of carboxymethyl cellulose and polyvinylidene fluoride.
[0071] In the present application, the proportions of the binder and the conductive agent in the first coating and the second coating are within the above range, which can make the upper and lower coatings of the negative electrode plate have a strong bonding strength. When subjected to external forces or environmental changes, the coating is not prone to problems such as stratification and peeling, thereby improving the stability and reliability of the coating; at the same time, it can simplify the preparation process, reduce production difficulty, and improve production efficiency. The conductive agent in the first coating is preferably acetylene black and conductive carbon black because the two have good conductivity, can form a good conductive network, and enhance the conductivity between the first coating and the current collector; the binder is preferably styrene-butadiene rubber latex, carboxymethyl cellulose, and polyacrylic acid, which can effectively improve the bonding force between the first coating and the current collector; the conductive agent in the second coating is preferably carbon nanotubes and composite conductive materials. Carbon nanotubes have high conductivity, and composite conductive materials can achieve the purpose of improving conductivity through compounding, thereby improving the conductivity of the second coating; the second binder is preferably polyvinylidene fluoride and carboxymethyl cellulose. Polyvinylidene fluoride has a high dielectric constant, stable chemical properties, can withstand swelling and corrosion of the electrolyte, and maintain the bonding force between the first and second coatings. Carboxymethyl cellulose has a good dispersing effect on graphite, which is beneficial to the uniformity and stability of the slurry of graphite-coated hard carbon materials.
[0072] Those skilled in the art can understand that the above-mentioned secondary battery also includes a positive electrode plate, a separator, an electrolyte and a casing, etc. During the battery charging and discharging process, metal ions (sodium ions) are embedded and released back and forth between the positive electrode plate and the negative electrode plate, and the electrolyte plays the role of conducting ions between the positive electrode plate and the negative electrode plate. The separator is arranged between the positive electrode plate and the negative electrode plate, which mainly plays the role of preventing the positive and negative electrodes from short-circuiting, and at the same time allows metal ions to pass through.
[0073] As an example, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer. The negative electrode current collector has two surfaces opposite to each other in its thickness direction. The negative electrode active material layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0074] The electrolyte used in the secondary battery of the present application may include any technology disclosed in the prior art. As an example, it may include an organic solvent, a sodium salt and an additive, wherein the organic solvent includes but is not limited to at least one of ethylene carbonate, propylene carbonate and diethyl carbonate; the lithium salt includes but is not limited to at least one of sodium hexafluorophosphate, sodium tetrafluoroborate and sodium hexafluoroarsenic phosphate; the additive includes but is not limited to at least one of a film-forming additive, a conductive additive and a flame retardant additive.
[0075] According to another aspect of the present application, there is provided an electrical device comprising the above-mentioned secondary battery.
[0076] It is understandable that the secondary battery can be used as a power source for the electrical equipment or as an energy storage unit for the electrical equipment. The electrical equipment may be, but is not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0077] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0078] Example 1
[0079] This embodiment provides a negative electrode sheet, the composition and preparation method of which are as follows:
[0080] Preparation of the first active substance: 3% by mass of silicon powder (calculated by the mass of silicon element in the silicon source) is ball-milled with coal-based soft carbon and bio-based hard carbon. The Dv50 of the coal-based soft carbon is 6μm; the Dv50 of the biomass hard carbon material is 3μm, the mass ratio of coal-based soft carbon to bio-based hard carbon is 2:8, and the ball-milling time is 10h to disperse the silicon source in the mixed material. The material after ball milling is heat-treated at 1000°C to obtain a soft and hard carbon composite material, namely the first active substance; the first active substance is subjected to thermogravimetric analysis under an inert gas atmosphere, the test temperature is 30-500°C, the heating rate is 10°C / min, and the weight loss percentage of the first active substance in the temperature range of 200°C to 400°C is 3%.
[0081] Preparation of the second active substance: ball-milling sulfur powder (based on the mass of sulfur element in the sulfur source) and phosphorus pentoxide (based on the mass of phosphorus element in the phosphorus source) with a mass ratio of 1% with bio-based hard carbon to disperse the sulfur source and the phosphorus source in the hard carbon, and heat-treating the above materials at 600°C for 5 hours to obtain a hard carbon material containing 1% sulfur and 1% phosphorus; adding the doped hard carbon to 10 mg / mL hexadecyltrimethylammonium bromide (CTAB), stirring and soaking at room temperature for 6 hours, and drying to obtain treated hard carbon; mixing the treated hard carbon material with graphite in a mass ratio of 9:1 to obtain a second active substance; the Dv50 of the second active substance is 8μm; performing thermogravimetric analysis on the second active substance in an inert gas atmosphere, the test temperature is 30-500°C, the heating rate is 10°C / min, and the weight loss percentage of the second active substance in the temperature range of 200°C to 400°C is 2%.
[0082] First coating: The non-metallic element nitrogen-doped first active material prepared by the above method (the powder resistivity was tested to be 7.8 mΩ·cm), acetylene black (as the first conductive agent), and styrene-butadiene rubber emulsion (as the first binder) were mixed in a mass ratio of 94:3:3, and deionized water was used as a solvent to prepare a slurry, which was coated on the negative electrode current collector copper foil (thickness of 6 μm), with a double-sided coating thickness of 112 μm (single-sided 56 μm), and the thickness of the first coating was controlled to be 60.54% of the total thickness, and the porosity of the first coating was 40%.
[0083] Second coating: The second negative electrode active material doped with sulfur and phosphorus (the powder resistivity was tested to be 6.4Ω·cm), carbon nanotubes (as the second conductive agent), and carboxymethyl cellulose (as the second binder) were mixed in a mass ratio of 94:3:3, and deionized water was used as a solvent to form a slurry, which was coated on the first coating. The total thickness of the second coating was controlled to be 73μm (single-side thickness was 36.5μm), accounting for 39.46% of the total thickness of the first coating and the second coating, and the porosity of the second coating was 20%.
[0084] After testing, the film resistance of the negative electrode sheet provided in this embodiment is 1.5 mΩ.
[0085] Example 2-Example 11
[0086] Compared with Example 1, Example 2 to Example 11 differ in that the preparation of the first coating is different, and the specific details are shown in the table below.
[0087] Table 1
[0088]
[0089]
[0090] Example 12-Example 19
[0091] Compared with Example 1, Examples 12 to 19 differ in that the preparation of the second coating is different, as shown in the table below.
[0092] Table 2
[0093]
[0094] Comparative Example 1
[0095] This comparative example provides a negative electrode plate, which is different from Example 1 in that the negative electrode plate is only coated with a first coating layer, and the thickness of the first coating layer is the same as the sum of the thickness of the first coating layer and the second coating layer in Example 1.
[0096] Comparative Example 2
[0097] This comparative example provides a negative electrode sheet, which is different from Example 1 in that no doping elements are added during the preparation of the first active material and the second active material.
[0098] Comparative Example 3
[0099] This comparative example provides a negative electrode plate, which is different from Example 1 in that the first active material and the second active material in the first coating layer and the second coating layer are both made of artificial graphite (model: BYD AGP S360), and the rest is the same as Example 1.
[0100] Test Case
[0101] The negative electrode plates provided in the above embodiments and comparative examples are applied to a sodium ion battery. The preparation method of the sodium ion battery is as follows:
[0102] The positive electrode sheet was prepared as follows: Weigh the positive electrode active material NaNi with a mass ratio of 97.3:0.5:1.2:1.0 1 / 3Fe 1 / 3 Mn 1 / 3 O2, SP, PVDF and carbon nanotubes are added with an appropriate amount of NMP to prepare a slurry which is coated on both sides of the positive electrode current collector aluminum foil and dried to obtain a positive electrode sheet with a double-sided coating thickness of 138 μm.
[0103] A battery (battery capacity 2Ah) was prepared by combining the positive electrode plate, the separator, the electrolyte (a mixture of a NaPF6 solution with a concentration of 1 mol / L, solvents ethylene carbonate, propylene carbonate and diethyl carbonate in a volume ratio of 1:1:1) and the negative electrode plate provided in the above embodiments and comparative examples, and a cycle test was carried out on a charge and discharge test machine.
[0104] Electrical performance test method:
[0105] The battery obtained by the above method was subjected to charge and discharge test after being divided into capacities. The battery was charged and discharged at a constant current of 1C, with an operating voltage of 1.8 to 3.9V, a test temperature of 25°C, and cycled at room temperature for 500 cycles. After the cycle was completed, the capacity retention rate was calculated, and the capacity retention rate = discharge capacity of the Nth cycle / first discharge capacity × 100%.
[0106] First coulombic efficiency = first discharge capacity / first charge capacity × 100%.
[0107] Energy density = first discharge energy / battery mass.
[0108] The specific test results are shown in the table below:
[0109] Table 3
[0110] Group Energy density, Wh / kg First coulombic efficiency, % 500 cycles capacity retention, % Example 1 150.5 90.6 98.0 Example 2 155.3 92.0 97.6 Example 3 150.4 93.3 96.3 Example 4 152.2 95.7 99.5 Example 5 151.0 92.4 98.5 Example 6 152.1 93.3 99.6 Example 7 153.2 94.5 99.3 Example 8 153.5 92.5 98.7 Example 9 149.8 94.2 97.4 Example 10 149.4 92.8 98.4 Embodiment 11 151.5 94.2 99.6 Example 12 148.9 91.9 97.6 Example 13 149.7 93.2 98.3 Embodiment 14 152.7 91.4 97.8 Embodiment 15 154.9 92.6 99.8 Example 16 151.3 93.8 97.0 Embodiment 17 152.6 93.0 99.4 Embodiment 18 152.5 92.5 95.8 Embodiment 19 152.1 93.4 99.5 Comparative Example 1 115.0 81.4 84.2 Comparative Example 2 128.2 85.5 88.6 Comparative Example 3 120.1 83.8 85.5
[0111] It can be seen from the test results in the above table that the negative electrode plate and sodium ion battery provided in the embodiments of the present application have a higher first coulombic efficiency and energy density, as well as better cycle performance. The selection of specific active materials in the embodiments and the double-coating structure can significantly improve the performance of the battery.
[0112] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A secondary battery, characterized in that: A negative electrode sheet is included, wherein the negative electrode sheet includes: current collector; A first coating layer, coated on at least one side of the current collector, wherein the first coating layer contains a first active material, wherein the first active material includes a soft carbon material and a first hard carbon material, and wherein the first active material contains a first element, wherein the first element includes at least one of nitrogen, sulfur, phosphorus, and silicon; A second coating is applied on the surface of the first coating, the second coating contains a second active substance, the second active substance includes a second hard carbon material, graphite material is distributed on at least part of the surface of the second hard carbon material, the second active substance contains a second element, and the second element includes at least one of nitrogen, sulfur, phosphorus, and silicon.
2. The secondary battery according to claim 1, characterized in that: The first element includes silicon, and at least one of nitrogen, sulfur, and phosphorus; And / or, the second element includes silicon, and at least one of nitrogen, sulfur, and phosphorus.
3. The secondary battery according to claim 1, characterized in that: Based on the total mass of the first active substance, the mass percentage of the soft carbon material is 20% to 50%, and the mass percentage of the first element is 1% to 5%; And / or, based on the total mass of the second active material, the mass percentage of the graphite material is 10% to 40%, and the mass percentage of the second element is 0.01% to 3%.
4. The secondary battery according to any one of claims 1 to 3, characterized in that: Under a test pressure of 20 kN, the powder resistivity A of the first active material and the powder resistivity B of the second active material satisfy the following relationship: 1.2≤A / B≤1.
8.
5. The secondary battery according to claim 4, characterized in that: The powder resistivity A of the first active material is 5 to 12 mΩ·cm; And / or, the powder resistivity B of the second active material is 3 to 8 mΩ·cm.
6. The secondary battery according to claim 1, characterized in that: The film resistance of the negative electrode plate is 1-3 mΩ.
7. The secondary battery according to claim 1, characterized in that: The Dv50 of the soft carbon material is 6 to 12 μm; the Dv50 of the first hard carbon material is 3 to 8 μm; And / or, the Dv50 of the second active material is 8 to 14 μm.
8. The secondary battery according to any one of claims 1 to 3 or 5 to 7, characterized in that: The first active material and the second active material are subjected to thermogravimetric analysis in an inert gas atmosphere at a test temperature of 30 to 500° C. and a heating rate of 10° C. / min, satisfying: The weight loss percentage of the first active substance in the temperature range of 200° C. to 400° C. is less than 5%; The weight loss percentage of the second active material in the temperature range of 200° C. to 400° C. is less than 3%.
9. The secondary battery according to claim 8, characterized in that: The porosity of the first coating layer is 40% to 50%, and the porosity of the second coating layer is 20% to 30%.
10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 9.
Citation Information
Patent Citations
Hard carbon negative electrode material of lithium ion battery, preparation method and application of hard carbon negative electrode material
CN102820455A
Negative electrode material and preparation method thereof, negative electrode and preparation method thereof, and sodium ion battery
CN116613292A
Negative electrode material and preparation method and application thereof
CN116960324A
Negative electrode material, preparation method and battery
CN117766733A
Sodium-ion battery negative plate and preparation method thereof
CN117976808A